The Mission - Joffe,Roland (Diliman, Quezon City : Viva Video Inc, 2003)
Ronald Joffe's award-winning film the mission tells the true story of two men-a man of sword (Robert De Niro) and a man of cloth (Jeremy Irons)- who are forced to work together to save an Indian tribe from slavery in the 18th century South Africa. Mendoza (De Niro) is a slave trader and a colonial imperialist who has murdered his own brother (Aidan Quinn). He seeks penance by becoming a missionary at father Gabriel's (Irons) mountaintop mission. Father Gabriel is a devout and idealistic man who extorts peaceful interaction with the natives and colonialists. The two must unite despite their differences to save the mission when Spain, portugal and the Catholic church begin the negotiations about the boundaries ... negotiation that will affect both the freedom of the natives and the well-being of the missionaries.